Sex-Specific Protective Effects of APOE ε2 on Cognitive Performance. (29th September 2020) - Lamonja-Vicente, Noemí; Dacosta-Aguayo, Rosalia; López-Olóriz, Jorge; Prades-Senovilla, Laia; Roig-Coll, Francesca; Castells-Sánchez, Alba; Soriano-Raya, Juan José; Clemente, Inmaculada; Miralbell, Júlia; Barrios, Maite; López-Cancio, Elena; Cáceres, Cynthia; et al.
Abstract: Apolipoprotein E ( APOE ) has an important role in the multiple trajectories of cognitive aging. However, environmental variables and other genes mediate the impact of APOE on cognition. Our main objective was to analyze the effect of APOE genotype on cognition and its interactions and relationships with sex, age, lipid profile, C-reactive protein, and Brain-derived neurotrophic factor ( BDNF ) genotype in a sample of 648 healthy participants over 50 years of age with a comprehensive neuropsychological assessment. Our results showed that APOE ε2 carriers performed better in the Verbal Memory ( p = .002) and Fluency Domains ( p = .001). When we studied the effect of sex, we observed that the beneficial effect of APOE ε2 on the normalized values of these cognitive domains occurred only in females (β = 0.735; 95% confidence interval, 0.396–1.074; p = 3.167·10 −5 and β = 0.568; 95% confidence interval, 0.276–0.861; p = 1.853·10 −4, respectively). Similarly, the sex-specific effects of APOE ε2 were further observed on lipidic and inflammation biomarkers. In the whole sample, APOE ε2 carriers showed significantly lower levels of total cholesterol, low-density lipoprotein cholesterol, and C-reactive protein. These differences were found only among females. Furthermore, total cholesterol and low-density lipoprotein cholesterol mediated the protective effect of APOE ε2 on cognition in the whole sample and total cholesterol in females, providing candidate physiological mechanisms for the observed genetic effects. Our results show that the neuroprotective role of APOE ε2 in cognition varies with sex and that the lipidic profile partially mediates this protection. Age-related cognitive and functional decline is a continuous biological process with different cognitive trajectories (1 ). Complex interactions between heritability, environmental influence, and cognitive functions in aging have been highlighted (2 ). In particular, genetic differences explain around 15%–25% of the variance in life expectancy (3 ). Therefore, the identification of susceptibility genes and their biological effects on cognitive aging is required to establish interindividual differences in this process and promote early personalized interventions to delay cognitive decline and minimize the financial burden of aging in the health care system.